Bosnia and Herzegovina : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper analyzes government spending in Bosnia and Herzegovina (BiH). The size of the public sector in BiH is one of the largest in the region, owing mainly to a complex and highly decentralized governance structure. BiH spends a greater share of public resources on current spending items, notably on wages and social transfers. Moreover, poorly targeted social benefits generate adverse incentives with respect to informality and labor force participation. To enhance economic growth, BiH will need to refocus its spending and increase its efficiency, chiefly on spending on human and physical capital.